2015
DOI: 10.17116/neiro201579572-76
|View full text |Cite
|
Sign up to set email alerts
|

MRI diagnosis of spinal metastasis of medulloblastoma. A clinical case and literature review

Abstract: Медуллобластома относится к эмбриональным опухолям и является самой частой злокачественной опухолью головного мозга у детей. Медуллобласто-мы метастазируют по путям ликвороциркуляции в головной и спинной мозг и в редких случаях распро-страняются за пределы центральной нервной систе-мы. Наличие метастазов опухоли на момент поста-новки диагноза ухудшает прогноз и требует прове-дения более агрессивного лечения.Магнитно-резонансная томография (МРТ) всех отделов центральной нервной системы с кон-трастным усилением … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Leptomeningeal dissemination tendency of medulloblastoma was clearly observed in this case, showing spinal and supratentorial seeding. Spinal metastatic deposit showed intradural extramedullary enhancing nodule, consistent with the statement of Ozerov et al 9 The presented case shown the presence of supratentorial seeding, although Lee et al, 3 stated that supratentorial seeding of medulloblastoma less often. Each supratentorial lesion originated in the area with close contact to the CSF, both suprasellar and sulci area lesions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Leptomeningeal dissemination tendency of medulloblastoma was clearly observed in this case, showing spinal and supratentorial seeding. Spinal metastatic deposit showed intradural extramedullary enhancing nodule, consistent with the statement of Ozerov et al 9 The presented case shown the presence of supratentorial seeding, although Lee et al, 3 stated that supratentorial seeding of medulloblastoma less often. Each supratentorial lesion originated in the area with close contact to the CSF, both suprasellar and sulci area lesions.…”
Section: Discussionsupporting
confidence: 88%
“…1 Medulloblastoma has a high tendency to disseminate through the CSF whether as a spinal deposit or supratentorial seeding. 1,3,9 Therefore, the final diagnosis of metastatic seeding of the temporal lobe of medulloblastoma was made in accordance with prior data of cerebellar tumor, information regarding multiple spinal and supratentorial metastatic seedings, the initial deposit of the temporal lobe, and histological findings.…”
Section: Discussionmentioning
confidence: 96%
“…If this cannot be done, early postoperative MRI within 72 hr is recommended to avoid nonneoplastic contrast enhancement due to surgical manipulation . Postoperative MRI may be difficult to interpret, as changes including contrast enhancement such as postoperative contrast‐enhancing meningeal thickening or clumping of the nerve roots may be seen due to blood products within the spinal canal, inflammatory changes, and shifts in pressure …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Postoperative MRI may be difficult to interpret, as changes including contrast enhancement such as postoperative contrast-enhancing meningeal thickening or clumping of the nerve roots may be seen due to blood products within the spinal canal, inflammatory changes, and shifts in pressure. 1,6,10 The description of abnormalities such as linear vascular enhancement, nerve root enhancement, and clumping of the nerve roots by neuroradiologists on pre-and/or postoperative diagnostic spinal MRI prompted this review to investigate the frequency and diagnostic significance of these "equivocal findings" in the absence of the evidence of spinal nodular metastasis or leptomeningeal spread. The goal of our study was to describe equivocal findings and evaluate its association with staging results, treatment assignment to average risk versus high risk and overall survival (OS) in children older than 3 years of age diagnosed with MB.…”
Section: Introductionmentioning
confidence: 99%